TYPOLOGY OF PHONOLOGICAL SYSTEMS OF MODERN SLAVIC LANGUAGES: ACOUSTIC DIMENSION - Юсип-Якимович, Юлія (Linguistic Bulletin (Movoznavchyi Visnyk), 2019)
The article is devoted to the typology of phonological systems of modern Slavic languages, in particular acoustic measurement. The study is a continuation of studies by the author of phonological systems of the Slavic languages through the prism of historical laws: the problem of genetic typology; phonological systems of Slavic languages through the prism of phonological universals: to the problem of synchronous typology. The subject of consideration is phonological acoustic typology, which has always been on the periphery of linguists’ interests. Typological phonology is known to have been founded by the Prague Structural School. The typology of phonological systems of a large number of languages was worked out by M.S. Trubetskoi. The methodological basis of our study was the principles of the Prague Structural School (Theses of the Prague Linguistic Circle). R. Jacobson established specific linguistic universals – a scale of differential characteristics as elementary phonological units, through which one can describe the phonemes of any of the languages. Internal recognition signs, which appear in the languages of the world, are reduced, according to R. Jacobson, to twelve binary oppositions. They make it possible to stratify phonological systems and reduce their diversity to a limited set of types. The acoustic dimension of the 12 acoustic features of the Slavic languages singed by R. Jacobson was made by us on the following grounds: 1) vocal –unvocal; 2) consonant – non-consonant; 3) compactness – non-compactness; 4) diffusion – non-diffusion; 5) peripheralism – nonperipheralism; 6) intermittence – non intermittence; 7) diesis tone – simple tone; 8) tension – non-tension; 9) nasal –non-nasal); 10) marking; 11) callousness – deafness; 12) longitude – shortness; 13) palatalism – nonpalatalism; 14) sharpness – non-sharpness. For the convenience of acoustic dimension, the sign diffusion – compactness is divided into two paired signs; diffusion – non-diffusion and compactness – non-compactness and one prosodic sign such as longitude. 60 Purpose. The linguistic space covered by the Slavic languages is constructed as one model consisting of models of individual Slavic languages. The image of the phonological systems of the Slavic languages in the form of a system of recognizable signs allows placing Slavic languages into a single, multi sign space, where the phonological distinctive features serve as parameters. Originality. The identification of recognition features and elements, formulated more often in acoustic terms, is based on a theoretical representation of their acoustic nature, backed up by universally recognized relations between the acoustic and articulatory side of the sounds of language. Since articulation correlates with the acoustic phenomenon in the same way as the means with the result, the classification of articulation data is carried out taking into account the acoustic system. Conclusion. Scientific novelty of research results of the study is the schemes of acoustic measurement of each of the modern Slavic languages.